Next-generation sodium alginate hydrogels for heavy metal ion removal: Properties, dynamic adsorption–desorption mechanisms, and sustainable application potential - Ling, Felicia Wen Xia; Rovina Kobun; Sarifah Supri; Patricia Matanjun; Siti Faridah Mohd Amin; Mohd Nazri Abdul Rahman (Springer Verlag, 2025)
Heavy metal contamination constitutes a significant global environmental issue, primarily attributable to industrial operations. Adsorption is one of many techniques used to clean up pollution, and it has become an environmentally friendly and cost-effective way to remove heavy metals from industrial wastewater. This review assesses the efficacy of sodium alginate hydrogels, a naturally sourced biopolymer, in eliminating heavy metal ions from aqueous solutions. Biocompatibility, non-toxicity, and high adsorption capacity of sodium alginate hydrogels make it an attractive candidate for environmental applications, particularly in water treatment. The heavy metal elimination primarily occurs through adsorption, which involves mechanisms such as ion exchange, complexation, chelation, electrostatic interactions, and hydrogen bonding. These processes work synergistically to enhance the hydrogels' effectiveness in capturing heavy metal ions. This review also highlights the regeneration and reusability of adsorbent that allows for multiple cycles of use without needing constant replacement. Besides laboratory studies, the practical applications of sodium alginate hydrogels in extensive environmental remediation, including wastewater treatment and industrial effluent management, are examined. The feasibility of incorporating these hydrogels into current water treatment systems is thoroughly evaluated alongside scalability considerations. Challenges and future directions are also addressed, emphasizing the need to enhance the performance of sodium alginate hydrogels through structural modifications, composite formation, and synergistic materials. This review aims to comprehensively understand sodium alginate hydrogels' role in heavy metal removal, providing valuable insights for researchers and practitioners in food science, technology, and environmental management.